Efektifitas Pembelajaran Kalam Menggunakan Modul Berdasarkan Pendekatan Kontekstual - Zen, Aatina Khairal Athiyyah; Danial Hilmi (Tarling : Journal of Language Education, 2025)
This study aims to examine the effectiveness of kalam learning by using contextual-based teaching modules at Al-Amanah Al-Gontory Islamic Boarding School, South Tangerang. The background of this study id the obstacles in learning kalam which still uses traditional methods and the lack of teaching materials that are in accordance with the context of the daily lives of students. This study used a quantitative approach with a quasi-eksperimental method with a pretest-posttest control group design. The population in this study were all third grade students of Al-Amanah Al-Gontory Boarding School with a total of 185 students. The research sample consisted of two classes, namely class III A with 20 students as the esperimental class and class III B with 20 students as the control class. Data collection methods used observation, documentation ans tests. Data analysis used normality test, T-test (independent sample t test) and N-gain analysis. The results showed that the results of the T-test an N-gain analysis showed a significant difference between the learning outcomes of the experimental and control groups. The average N-gain of the experimental group is 77,04% and can be said to be effective. While he control group only reached 10,81% which is included in the ineffective category. This data shows that the use of modules based on contextual approaches can significantly improve students’ speaking skills.